Expanding mpox surveillance: a community-centric approach using discarded condoms - Sahay, Rima R.; Shete, Anita M.; Aggarwal, Sumit; Patil, Deepak Y.; Yadav, Pragya D. (International Journal Of Community Medicine And Public Health, 2025)
Within short span of two years, the WHO has declared emergence of mpox as Public health emergency of international concern (PHEIC) in 2022 and 2024. As Mpox challenges the global public health system, traditional surveillance emerges as inadequate in sensitizing marginalized populations and those at elevated risk in high-risk categories. The fact that this gap exists calls for innovative and community centered approaches to inclusive, equitable, and effective public health responses.